The spitting image : myth, memory, and the legacy of Vietnam - Lembcke, Jerry, 1943- (New York University Press, 1998)
"One of the most resilient images of the Vietnam era is that of the anti-war protester - often a woman - spitting on the uniformed veteran just off the plane. The lingering potency of this icon was evident during the Gulf War, when war supporters invoked it to discredit their opposition." "In this startling book, Jerry Lembcke demonstrates that not a single incident of this sort has been convincingly documented. Rather, the anti-war Left saw in veterans a natural ally, and the relationship between anti-war forces and most veterans was defined by mutual support." "While veterans were sometimes made to feel uncomfortable about their service, this sense of unease was, Lembcke argues, more often rooted in the political practices of the Right."--Jacket